Hermeneutic phenomenological interpretations of patients with head and neck neoplasm experiences living with radiation-induced xerostomia: the price to pay? - Charalambous, Andreas (My University, 2014)
Purpose: Patients with head and neck neoplasms often experience a number of persistent treatment related symptoms including xerostomia. The impact of xerostomia can be profound and wearing on the patients, hence negatively influencing their quality of life. The purpose of this study was to explore the in-depth experiences of the patients living with radiation-induced xerostomia. Methods and sample: This was a hermeneutic phenomenological study inspired by the Philosophy of Paul Ricoeur. Research data were retrieved with individual narratives from 15 patients diagnosed with head and neck neoplasm that underwent radiotherapy. Interpretation proceeded through three phases: naïve reading, structural analysis and comprehensive understanding. Results: Five themes consisting of ten sub-themes emerged from the narratives reflecting on the patients’ lived experiences. The themes were “suffering of the body”, “suffering of the person’s world”, “being helpless against xerostomia”, “suffering of the mind” and “being alone”. The comprehensive understanding disclosed new possibilities for being-in-the world in relation to living with xerostomia. Conclusion: The precedent consideration of xerostomia mainly as a physical side-effect of radiotherapy was outweighed by the social and psychological effects revealed by this study. These xerostomia’s effects are inflicted on the patients with an obvious reflection on their perceived quality of life. The findings call upon a shift towards acknowledging the severity of xerostomia and the need to care for these patients holistically.
Keywords: Qualitative research; Head and neck neoplasms; Narratives; Xerostomia; Paul ricoeur; Narratives; Quality of life; Social isolation